Dual targeting of EZH2 and PD-L1 in Burkitt’s lymphoma enhances immune activation and induces apoptotic pathway - Jeong, Yurim; Jang, Hyewon; Kim, Se Been; Yu, Minseo; Kim, Ra Eun; Choi, Wan-Su; Jeon, Youngwoo; Lim, Jung-Yeon (Frontiers in Immunology, 2025)
IntroductionEnhancer of zeste homolog 2 (EZH2) catalyzes H3K27me3, an epigenetic modification linked to gene silencing, and its overexpression contributes to the progression of hematological malignancies. This study compares the efficacy of a conventional EZH2 inhibitor with a PROTAC-based EZH2 degrader in human lymphoma cell lines. Furthermore, we investigate the anti-tumor effects of combining EZH2 degrader with anti-PD-1, an immune checkpoint inhibitor, focusing on immune cell interactions and underlying mechanisms. MethodsThe cytotoxic effects of the EZH2 degrader and EZH2 inhibitor were evaluated in Burkitt’s, B-cell, cutaneous T-cell, and Hodgkin’s lymphoma cell lines. Additionally, the combination therapy of the EZH2 degrader and anti-PD-1 was assessed both in vitro and in a hu-PBMC-CDX mouse model. ResultsWe evaluated the effects of an EZH2 degrader on seven lymphoma cell lines and observed significant reductions in cell viability compared to EZH2 inhibitor, particularly in Burkitt’s lymphoma cell lines. EZH2 degrader treatment reduced EZH2 and c-Myc expression, induced G2/M cell cycle arrest, and increased apoptosis markers, including cleaved caspase-3 and cleaved PARP. Furthermore, Burkitt’s lymphoma is a PD-L1 negative tumor; however, treatment with the EZH2 degrader resulted in a slight increase in PD-L1 expression. Combining EZH2 degrader with anti-PD-1 significantly enhanced anti-tumor effects compared to monotherapy. In vivo studies using a humanized lymphoma mouse model demonstrated a synergistic anti-tumor effect of EZH2 degrader and anti-PD-1, which was attributed to apoptosis-related pathways. DiscussionThese findings aim to provide insights into the therapeutic potential of targeting EZH2 in combination with immune checkpoint inhibitors for improved treatment of lymphomas.